2007
DOI: 10.1174/021037007780705210
|View full text |Cite
|
Sign up to set email alerts
|

Los errores sintácticos al escribir numerales en rango superior

Abstract: El objetivo de este artículo es analizar los errores sintácticos que niños de 1º, 2º y 3º grado de primaria cometen cuando escriben numerales dictados con un rango superior al aprendido. Sus producciones se caracterizaron en función de la manera como escriben los componentes del numeral arábigo dictado y del tipo de relaciones que utilizan para unirlos. La progresiva disminución del error sintáctico a través de los grados y la modificación de las relaciones utilizadas al escribir los componentes del numeral a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
1
1
0
10
Order By: Relevance
“…Similar to the findings of [1,26,46,47] our results indicated that Portuguese students in elementary grades committed more prerequisite linguistic errors than vocabulary type errors in Translating Numbers Tasks. Students' prerequisite linguistic errors involved reading digits without considering their place value, ignoring order magnitude from left to right, misinterpreting zeroes and commas, and adding or omitting number words in relation to the number of digits in the numeral.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the findings of [1,26,46,47] our results indicated that Portuguese students in elementary grades committed more prerequisite linguistic errors than vocabulary type errors in Translating Numbers Tasks. Students' prerequisite linguistic errors involved reading digits without considering their place value, ignoring order magnitude from left to right, misinterpreting zeroes and commas, and adding or omitting number words in relation to the number of digits in the numeral.…”
Section: Discussionsupporting
confidence: 90%
“…Our study also identified researches that focus on the conceptual fields of addition and multiplicative relationships: for instance, in the management of knowledge instruments and in the execution of intellectual operations using decimal numbers, leading to the design and implementation of didactic strategies from real or specific, graphic and symbolic stages. In this regard, Hederich-Martínez et al (2016) and Orozco, Guerrero, and Otálora (2007) discuss characteristics of numerals associated with the difficulty of their transcoding. Understanding the nature of the task of transcoding numerals, or the ‘dictating numbers task’, is essential for the interpretation of children’s errors, as well as for choosing more appropriate evaluation designs, suited to the particularities and characteristics of children during the development stages in which that task is the objective of mathematical education.…”
Section: Resultsmentioning
confidence: 99%
“…Codificación en fragmentos del numeral verbal, con la unión de dos o más numerales arábigos formalmente correctos. Por ejemplo, se dicta "Ochocientos noventa y cinco" y se escribe "800905" (Orozco, Guerrero y Otálora, 2007).…”
Section: Yuxtaposiciónunclassified
“…Codificación del numeral verbal caracterizada por sobre escribir un fragmento de orden inferior en el último dígito de un fragmento de orden superior. Por ejemplo, se dicta "trescientos cuarenta", y se escribe "3040" (Orozco, Guerrero y Otálora, 2007).…”
Section: Compactaciónunclassified
See 1 more Smart Citation